Pengaruh Emotional Marketing Dan Experiential Marketing Terhadap Loyalitas Pelanggan (Studi Pada Bebek Sinjai Bangkalan) - M. Zainal; N. Rachma; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This study's goal is to determine how experiential marketing and emotional marketing influence consumer loyalty. Quantitative descriptive research is the method employed. Consumers of the Bangkalan Sinjay duck make up the study's sample. and 50 people from the population that was not determined by using 25 times as many variables as the sample size are used. According to the study's findings, customer loyalty is significantly impacted by both emotional and experiential marketing at the same time. and variables that are only partially independent significantly impact the dependent variable. Keywords: consumer loyalty, emotional marketing and experiential marketing